Life-Threatening Rupture of an Idiopathic Left Hepatic Artery Pseudoaneurysm Successfully Treated with Endovascular Coil Embolization - Jorge E. Sandelis-Pérez; Andrés Córdova-Toro; Steven García-Santiago; Erica G. Otero-Cárdenas; Pedro Gil de Rubio-Cruz; Suheiry Márquez-Márquez; Mary J. Rodríguez-Malavé; Arelis Febles-Negrón; José A. Colon-Márquez; Alejandro Hidalgo-Ríos (Case Reports in Vascular Medicine)
Hepatic artery pseudoaneurysm is a rare condition; they are multifactorial, most of them locating in the extrahepatic vasculature and the mortality associated to its rupture may reach up to 70%. We report a 77 years old female who was admitted due to headache and uncontrolled hypertension and that on her second hospital day developed sudden hemodynamic instability, abdominal pain, fatigue, skin-mucosa pallor, and anemia. Abdominal CT scan with contrast showed a left hepatic artery pseudoaneurysm associated with extensive hemoperitoneum. Patient required emergent hemodynamic stabilization and finally was treated successfully with a superselective endovascular coil embolization. Our patient represents an atypical case of a spontaneous rupture of an idiopathic hepatic artery pseudoaneurysm. Hence, the importance of having a high index of clinical suspicion. Endovascular coil embolization has become the first-line treatment.